Pengaruh Model Pembelajaran Cooperative Learning Tipe Jigsaw Terhadap Keaktifan Belajar Pendidikan Agama Kristen Siswa Kelas XI SMA Negeri 1 Ronggurnihuta Kabupaten Samosir Tahun Pembelajaran 2023/2024 - Dina Siahaan C.F (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The study aims to determine the positive and significant influence of the jigsaw-type cooperative learning model on the learning activity of grade XI students of SMA Negeri 1 Ronggurnihuta for the 2023/2024 Learning Year. The research hypothesis is that there is a positive and significant influence between the jigsaw-type cooperative learning model on the learning activity of grade XI students of SMA Negeri 1 Ronggurnihuta, Samosir Regency for the 2023/2024 Learning Year. Descriptive quantitative research methods of inferential statistics. The population of all grade XI students of SMA Negeri 1 Ronggurnihuta for the 2023/2024 Learning Year who are Protestant Christians is 174 people. Random sampling is 30% of the total population, which is 52 people. The research instrument is in the form of a closed questionnaire. The results of the analysis requirements obtained a value of rxy=0.791>rtabel=0.226 and tcalc=9.142>ttabel=2.000 showed a relationship between the jigsaw-type cooperative learning model and the learning activity of grade XI students of SMA Negeri 1 Ronggurnihuta Learning Year 2023/2024 and obtained a regression equation. Test the hypothesis obtained Fcalculate = 83.776 > Ftable = 1.39 then H0 is rejected and Ha is accepted. The study concluded that there was a positive and significant influence between the jigsaw-type cooperative learning model on the learning activity of grade XI students of SMA Negeri 1 Ronggurnihuta, Samosir Regency for the 2023/2024 Learning Year of 62.57%.